Etiological and clinical features of infectious complications in hemoblastosis - V. N. Chebotkevich; V. V. Burylev; E. I. Kaytandzhan; S. S. Bessmeltsev; E. R. Shilova; S. B. Yatsyshina; A. V. Kudryavtseva (Онкогематология)
The aim of the study was to analyze the etiologys of infectious complications (especially the role of respiratory viruses in patients with haematological malignancies).   The supervised patients were divided into two subgroups: the first was patients with hemoblastosis and clinically evidence of infectious complications (n = 50), and the second – patients without clinical features of infection (control group) (n = 35). We analyzed the pharyngeal flora of patients by means of bacteriological and mycological methods and the frequency of respiratory viruses (Respiratory syncytial virus, Influenza A and B, Parainfluenza – 1, 2, 3, 4, rhinoviruses, adenoviruses, coronaviruses, metapneumovirus, bocavirus); herpesviruses (herpes simplex type 1 and 2, herpes type 6, Epstein-Barr virus and Cytomegalovirus), Mycoplasma pneumoniae and Chlamydophila pneumoniae by means of PCR. Respiratory infections were detected in 62 % in subgroup with clinically evidence of infectious complications and only in 22.8 % in the second subgroup. In many cases herpesvirus infection (Epstein-Barr virus and Cytomegalovirus) was associated with respiratory viral infections. So, respiratory and herpes viral infections must be carefully controlled in immunosuppressed patients with hematological malignancies.